Kualitas Produk,Lokasi,Loyalitas Pelanggan,Kepuasan Konsumen di Kosmetik H.Amd Aziz - Febi agustina; Emil salim; Della asmaria putri (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to determine the influence of product quality and location on customer loyalty through customer satisfaction as an intervening variable at H. Amd Aziz Cosmetics in Solok City. The research method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) 3.0, using a questionnaire with 100 respondents. The results of the data analysis indicate that there is a positive and significant influence of product quality on customer satisfaction. There is a positive and significant influence of location on customer satisfaction. There is a positive and significant influence of product quality on customer loyalty. There is a positive and significant influence of location on customer loyalty. There is a positive and significant influence of customer satisfaction on customer loyalty. There is a positive and significant influence of product quality on customer loyalty through customer satisfaction as an intervening variable. The influence of product quality on customer loyalty and the influence of location on customer loyalty at H. Amd Aziz Cosmetics in Solok City.